Analisis Pengaruh Pelatihan Dan Kompensasi Terhadap Kepuasan Kerja Pegawai Di Badan Penanggulangan Bencana Daerah Kabupaten Tapanuli Tengah - Simanjuntak, Deni Hendra; Absah, Yenni; Lubis, Arlina Nurbaity (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
The purpose of this study is to find out and to analyze the effect of training and compensation on job satisfaction at the Regional Disaster Relief Agency in Central Tapanuli Regency. The population in this research was 105 people and the sample was taken was 51 people. The data will be collected using both questionnaires and interviews. Questionnaires will firstly be tested using validity and reliability test. The analysis method which is/was used was multiple linear regressions. Based on the result of the research, it is known that training and compensation positively affect employee satisfaction; partially, training affects employees’ satisfaction positively and significantly, dominant compensation variable affects employees’ satisfaction which means that compensation variable influence more than training in increasing employee satisfaction